Ruídos clássicos ou a sangria antiga em 'Nadar na Piscina dos Pequenos' - Gomes, Daniel de Oliveira (eLyra, 2020)
Golgona Anghel’s poetry suggests criticism of the modern liquid world, where the subject is regulated by superficial relationships and the monotony of everyday life. She works on the issue of success and infamy, seeking the place of infamy as her paradoxical compass. In this essay, we investigate her appropriation of the classics, especially her references to the Greeks, seeking to analyze several aspects of the book Nadar na Piscina dos Pequenos, released in 2017.